KALIMAT TANYA DALAM PERSIDANGAN DI PENGADILAN NEGERI BANDA ACEH - Rahmad Nuthihar; Tara Astika Bangun; Wahdaniah Wahdaniah (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
This study examines the use of interrogative sentences in trials at the Banda Aceh District Court. The trial in principle is an activity to obtain and prove the information being tried. Therefore, the judge as the person in charge of examining and adjudicating cases uses question sentences to obtain information as clearly as possible. The results of this study conclude that the types of question sentences contained in the trials at the Banda Aceh District Court are, partial sentences, total sentences, rhetorical sentences, and subtle sentences. Furthermore, the question sentence function is a representative and directive function.